Nineteenth-century religion, literature and society. Volume III, Religious feeling - Dwor, Richa; Hetherington, Naomi, 1973- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
Part of a four-volume set, this third volume looks at 'religious feeling' as an important and distinct category for understanding the ways in which religion is embodied and expressed in culture. The complete four-volume historical resource provides new opportunities for investigating the relationship between religion, literature and society in Britain and its imperial territories by making accessible a diverse selection of harder-to-find primary sources. These include religious fiction, poetry, essays, memoirs, sermons, travel writing, religious ephemera, unpublished notebooks and pamphlet literature. Spanning the long nineteenth century (c.1789-1914), the resource departs from older models of 'the Victorian crisis of faith' in order to open up new ways of conceptualising religion.
38 Extract from Sentiments on Resignation (1807) -- 39 Extract from R. O. (ed.), Practical Piety Set Forth by St. Francis de Sales (trans. 1851) -- 40 Selections from Charlotte Elliott, Poems of Charlotte Elliott (1873) -- 41 Selection from Alice Lucas, ed. The Jewish Year (1898) -- Part 15 Thanksgiving -- 42 Extract from D. [David] Meldola, Form of Prayer and Thanksgiving to be Said in the Spanish and Portuguese Jews' Synagogue (1840) -- 43 Thomas [Griffiths], 'The Late Attempt on the Queen's Life' (1842) -- 44 Agasias, 'The Form of Thanksgiving' (1854) -- Part 16 Piety -- 45 Extract from William Ellery Channing, The Power of Unitarian Christianity to Produce an Enlightened and Fervent Piety (1840) -- 46 Extract from Gustavus D. Pike, 'The First Visit to London', in The Story of the Jubilee Singers: With their Songs (1875).
Richa Dwor is an Instructor in the English Department at Douglas College in New Westminster, Canada.
Online resource; title from digital title page (viewed on January 08, 2021).
eBooks on EBSCOhost
Keywords: Great Britain -- Religion -- 19th century -- Sources; Emotions -- Religious aspects -- History -- 19th century -- Sources; English literature -- 19th century -- History and criticism; Religious literature, English -- 19th century -- History and criticism; Religion and literature -- Great Britain -- History -- 19th century; Religion in literature; Grande-Bretagne -- Religion -- 19e siècle -- Sources; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature religieuse anglaise -- 19e siècle -- Histoire et critique; Religion et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Religion dans la littérature.; HISTORY -- Modern -- 19th Century; Religion; Emotions -- Religious aspects; English literature; Religion and literature; Religion in literature; Religious literature, English; Great Britain; 1800-1899; Sources; Criticism, interpretation, etc; History